Utilization of Paku Uban (Nephrolepis biserrata) Extract as a Molting Stimulant of Mud Crabs (Scylla spp.) in Traditional Ponds - Diana Maulianawati; Rukisah Rukisah; Awaludin Awaludin; Muhammad Iswan Guntur (Faculty of Fisheries and Marine Universitas Airlangga, 2020)
HighlightsThe Paku Uban (Nephrolepis biserrata) was identified and analyzedThe ability of paku uban to stimulated molting process of Scylla sp was analyzedThe paku uban (Nephrolepis biserrata) could increase the presentation of molting and accelerate molting processAbstractMud crab (Scylla spp.) is a fishery commodity with high economic value. For this reason, efforts to increase production are required with a more effective applicative technology. This study aims to determine the molting response and survival rate of mud crabs injected with paku uban leaf extract (N. biserrata) at different doses. The study was conducted for 30 days, located in Tibi Island, Tanah Lia District, Tanah Tidung. The design used in this study was a completely randomized design (CRD) with five treatments and eight replicates. Mud crabs weighing 80 - 150 g were tested in K1 (without injection), K2 (controlled injection), P1 (100 ppm extract), P2 (125 ppm extract) and P3 (150 ppm extract). The effectivity of paku uban (N. biserrata) extract with the highest percentage of molting of 50% took place at P3, 37.5% at P2, and 25% at P1. The lowest levels of molting percentage were at K1 and K2 by 0%. The fastest molting period was ten days at P2, and the longest was 29 days at P1. The highest weight growth reached 33.75 g at P3, followed by P2 and P1 with 31 and 18.75 g, respectively. The survival rate of mud crabs for all treatments reached 100%. The results of the analysis of variance indicated a significant bet effect (P < 0.05) on the molting and weight growth percentage. The BNT test suggested that a dose of 150 ppm was the optimum treatment.